2010
DOI: 10.1088/1475-7516/2010/03/009
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking dark matter through a non-minimal gravitational coupling with matter

Abstract: In this study one resorts to the phenomenology of models endowed with a non-minimal coupling between matter and geometry, in order to develop a mechanism through which dynamics similar to that due to the presence of dark matter is generated. As a first attempt, one tries to account for the flattening of the galaxy rotation curves as an effect of the non-(covariant) conservation of the energy-momentum tensor of visible matter. Afterwards, one assumes instead that this non-minimal coupling modifies the scalar cu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
132
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(139 citation statements)
references
References 53 publications
(75 reference statements)
7
132
0
Order By: Relevance
“…[23]. Analogous nonlinear gravitational couplings with a matter Lagrangian were also considered in the context of proposals to address the cosmic accelerated expansion [24], dark matter [25], in the analysis of the cosmological constant problem [26], the curvature-matter coupling viability has been analyzed from the point of view of the energy conditions and of their stability under the DolgovKawasaki criterion [27], and matter density perturbations were analyzed to constrain the curvature-matter coupling theory from growth factor and weak lensing observations [28]. In [29], modified gravity with a nonminimal curvature-matter coupling in the Palatini formulation was considered, and in [30], the f (R) type gravity models was generalized by assuming that the gravitational Lagrangian is given by an arbitrary function of the Ricci scalar R and of the matter Lagrangian L m .…”
Section: Introductionmentioning
confidence: 99%
“…[23]. Analogous nonlinear gravitational couplings with a matter Lagrangian were also considered in the context of proposals to address the cosmic accelerated expansion [24], dark matter [25], in the analysis of the cosmological constant problem [26], the curvature-matter coupling viability has been analyzed from the point of view of the energy conditions and of their stability under the DolgovKawasaki criterion [27], and matter density perturbations were analyzed to constrain the curvature-matter coupling theory from growth factor and weak lensing observations [28]. In [29], modified gravity with a nonminimal curvature-matter coupling in the Palatini formulation was considered, and in [30], the f (R) type gravity models was generalized by assuming that the gravitational Lagrangian is given by an arbitrary function of the Ricci scalar R and of the matter Lagrangian L m .…”
Section: Introductionmentioning
confidence: 99%
“…Taking n = −1, dark matter constraints require that R −1 ∼ (10 Gpc) −2 [20]. Thus, one obtains from Eq.…”
Section: Inverse Power-law Couplingmentioning
confidence: 99%
“…This possibility can have deep phenomenological implications: in particular, it would imply that regions with high curvature (which, in GR, are related to regions of high energy density or pressure) could lead to considera ble deviations from the dynamics predicted by Einstein's theory [17]. A wide range of results has arisen from this hypothesis, including the formal equivalence with a multi-scalar-tensor theory [18], the impact on solar observables [19], the possibility to account for dark matter [20], post-inflationary reheating [21] or the current accelerated expansion of the universe [22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these models allow for the mimicking of dark matter profiles in galaxies [10] and clusters of galaxies [11], as well as of dark energy at cosmological scales [12]. It was also shown that one can obtain somewhat more natural conditions for preheating in inflationary models [13] and that the coupling between curvature and matter is equivalent, under conditions, to an effective pressure which leads, in the weak field limit, to a generalized Newtonian potential [14].…”
Section: Nonminimally Coupled Matter-curvature Theories Of Gravitymentioning
confidence: 99%